2010
DOI: 10.1155/2010/310753
|View full text |Cite
|
Sign up to set email alerts
|

Connexin36 Gap Junction Blockade Is Ineffective at Reducing Seizure-Like Event Activity in Neocortical Mouse Slices

Abstract: Despite much research, there remains controversy over the role of gap junctions in seizure processes. Many studies report anticonvulsant effects of gap junction blockade, but contradictory results have also been reported. The aim of this study was to clarify the role of connexin36 (Cx36) gap junctions in neocortical seizures. We used the mouse neocortical slice preparation to investigate the effect of pharmacological (mefloquine) and genetic (Cx36 knockout mice (Cx36KO)) manipulation of Cx36 gap junctions on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 42 publications
0
11
0
Order By: Relevance
“…Additional complication in understanding Cx36‐mediated activity in seizures comes from studies that find it dispensable to seizure initiation and resistance. Mefloquine, a quinine derivative inhibitor of Cx36 and Cx50 GJs at low doses (Cruikshank et al, ), failed to elicit any change in seizure‐like event amplitude, frequency, or duration in low Mg 2+ – and aconitine‐treated neocortical slice preparations from wild type mice, compared to control treated and Cx36‐KOs (Voss et al, ). Similarly, in a 2011 study, Beaumont & Maccaferri () found that 4‐AP treated CA1 interneurons of Cx36‐KO mice exhibited no difference in epileptiform GABAergic currents relative to wild type nice despite uncoupling of interneurons across hippocampal strata.…”
Section: A Little Too Excited: Connexin and Pannexin Dysregulation Anmentioning
confidence: 99%
See 1 more Smart Citation
“…Additional complication in understanding Cx36‐mediated activity in seizures comes from studies that find it dispensable to seizure initiation and resistance. Mefloquine, a quinine derivative inhibitor of Cx36 and Cx50 GJs at low doses (Cruikshank et al, ), failed to elicit any change in seizure‐like event amplitude, frequency, or duration in low Mg 2+ – and aconitine‐treated neocortical slice preparations from wild type mice, compared to control treated and Cx36‐KOs (Voss et al, ). Similarly, in a 2011 study, Beaumont & Maccaferri () found that 4‐AP treated CA1 interneurons of Cx36‐KO mice exhibited no difference in epileptiform GABAergic currents relative to wild type nice despite uncoupling of interneurons across hippocampal strata.…”
Section: A Little Too Excited: Connexin and Pannexin Dysregulation Anmentioning
confidence: 99%
“…However, the contribution of Cx36-coupling to seizures remains uncertain due to disparate, and occasionally contrary, reporting. Studies utilizing global ablation of Cx36 GJs have yielded data indicating an anti-epileptogenic (Jacobson et al, 2010), proepileptogenic (Maier et al, 2002), and bystander (Beaumont & Maccaferri, 2011;Voss et al, 2010b) role for these molecules.…”
Section: Electrical Synapses In Seizuresmentioning
confidence: 99%
“…Jacobson et al (2010) found that Cx36 knockout mice exhibited an increase in seizurelike behaviors following the administration pentylenetetrazol (PTZ; a GABA(A)-receptor antagonist), indicating that normal expression of Cx36 may be protective against seizure-inducing conditions. However, this finding contradicts studies using the connexin blocking drug quinine, which found the drug either decreased the severity of seizures (Gajda et al, 2005), or showed no change (Voss, Mutsaerts, & Sleigh, 2010b). The discrepancy may potentially be due to the difference between chronic Cx36 deficiency (Cx36 knockout) versus acute Cx36 deficiency (quinine).…”
Section: Introductionmentioning
confidence: 84%
“…It is also possible that acute reduction of Cx36 is more detrimental than chronic knock down, meaning the acute reduction in Cx36 expression after hyperactivity, would be more detrimental than chronic knock-down. This difference may then also account for conflicting evidence in the field comparing chronic and acute knockdown of Cx36 (Gajda et al, 2005;Jacobson et al, 2010;Voss et al, 2010b). Taken together, these results suggest that the prevention of the loss of Cx36 function may prove to be a useful target for treating diseases of hyperactivity.…”
Section: Acute Reduction In Cx36 Functionality Leaves Organisms More mentioning
confidence: 99%
See 1 more Smart Citation